2012
DOI: 10.1095/biolreprod.111.092817
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Photoperiod and Nutrition and Its Effects on Seasonal Rhythms of Reproduction in the Ewe1

Abstract: In sheep, the seasonal patterns of reproductive activity are driven primarily by the annual photoperiodic cycle, but can also respond to other environmental factors, such as nutrition, yet little is known about the mechanisms underlying this interaction. This study was designed to define the interaction between photoperiodic and nutritional cues on seasonal patterns of ovarian activity, and to determine if there is a central interaction between these cues. Groups of Ile-de-France ewes were maintained in two nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Such a process bears critical adaptive value, best exemplified in species that hibernate (e.g., groundhog) or undergo daily torpor (e.g., Siberian hamster), which have evolved a strategy to build up abdominal fat depots during spring/summer to survive the harsh winter season (1, 61). Photoperiodic cues and the metabolic status interact in many seasonal breeders, including sheep (66, 67), goats (68, 69), and horses (70). In all these species, feeding modulates the duration of the breeding season and/or depth of the anestrus.…”
Section: Thyroid Hormone Signaling In Seasonal Cyclesmentioning
confidence: 99%
“…Such a process bears critical adaptive value, best exemplified in species that hibernate (e.g., groundhog) or undergo daily torpor (e.g., Siberian hamster), which have evolved a strategy to build up abdominal fat depots during spring/summer to survive the harsh winter season (1, 61). Photoperiodic cues and the metabolic status interact in many seasonal breeders, including sheep (66, 67), goats (68, 69), and horses (70). In all these species, feeding modulates the duration of the breeding season and/or depth of the anestrus.…”
Section: Thyroid Hormone Signaling In Seasonal Cyclesmentioning
confidence: 99%
“…These include food [53,54], social interactions [55], weather conditions [8] and especially ambient temperature [56]. In hibernating mammals, changes in temperature can advance phases within circannual rhythms.…”
Section: (D) Temperature and Other Factorsmentioning
confidence: 99%
“…Additional environmental factors such as photoperiod, nutrition and temperature also participate in the regulation of seasonal reproductive activity (Estrada-Cortés et al, 2009;Forcada & Abecia, 2006;Rosa & Bryant, 2003). Among these, photoperiod is regarded as the most important factor in the seasonal regulation of reproduction (Menassol, Collet, Chesneau, Malpaux, & Scaramuzzi, 2012;Nishiwaki-Ohkawa & Yoshimura, 2016). Numerous studies have confirmed that seasonal photoperiodic information is conveyed to the pineal gland through the retina.…”
Section: Introductionmentioning
confidence: 99%